A Comparison of Different Reagents Applicable for Destroying Halogenated Anionic Textile Dye Mordant Blue 9 in Polluted Aqueous Streams - Kamenická, Barbora; Weidlich, Tomáš (MDPI, 2023)
This article aimed to compare the degradation efficiencies of different reactants applicable for the oxidative or reductive degradation of a chlorinated anionic azo dye, Mordant Blue 9 (MB9). In this article, the broadly applied Fenton oxidation process was optimized for the oxidative treatment of MB9, and the obtained results were compared with other innovative chemical reduction methods. In the reductive degradation of MB9, we compared the efficiencies of different reductive agents such as Fe-0 (ZVI), Al-0, the Raney Al-Ni alloy, NaBH4, NaBH4/Na2S2O5, and other combinations of these reductants. The reductive methods aimed to reduce the azo bond together with the bound chlorine in the structure of MB9. The dechlorination of MB9 produces non-chlorinated aminophenols, which are more easily biodegradable in wastewater treatment plants (WWTPs) compared to their corresponding chlorinated aromatic compounds. The efficiencies of both the oxidative and reductive degradation processes were monitored by visible spectroscopy and determined based on the chemical oxygen demand (COD). The hydrodechlorination of MB9 to non-chlorinated products was expressed using the measurement of adsorbable organically bound halogens (AOXs) and controlled by LC-MS analyses. Optimally, 28 mol of H2SO4, 120 mol of H2O2, and 4 mol of FeSO4 should be applied per one mol of dissolved MB9 dye for a practically complete oxidative degradation after 20 h of action. On the other hand, the application of the Al-Ni alloy/NaOH (100 mol of Al in the Al-Ni alloy + 100 mol of NaOH per one mol of MB9) proceeded smoothly and seven-times faster than the Fenton reaction, consumed similar quantities of reagents, and produced dechlorinated aminophenols. The cost of the Al-Ni alloy/NaOH-based method could be decreased significantly by applying a pretreatment with Al-0/NaOH and a subsequent hydrodechlorination using smaller Al-Ni alloy doses. The homogeneous reduction accompanied by HDC using in situ produced Na2S2O4 (by the action of NaBH4/Na2S2O5) was an effective, rapid, and simple treatment method. This reductive system consumed quantities of reagents that are almost twice as low (66 mol of NaBH4 + 66 mol of Na2S2O5 + 18 mol of H2SO4 per one mol of MB9) in comparison with the other oxidative/reductive systems and allowed the effective and fast degradation of MB9 accompanied by the effective removal of AOX. A comparison of the oxidative and reductive methods for chlorinated acid azo dye MB9 degradation showed that an innovative combination of reduction methods offers a smooth, simple, and efficient degradation and hydrodehalogenation of chlorinated textile MB9 dye.
Srovnání rozdílných reakčních činidel aplikovatelných pro degradaci halogenoavného textilního barviva mordant Blue 9 z kontaminovaných vod
Keywords: acid azo dye; Mordant Blue 9; chlorophenol; Fenton oxidation; degradation; hydrodehalogenation; hydrodechlorination; NaBH4; Na2S2O5; Raney Al-Ni alloy; kyselá azobarviva; Mordant Blue 9; Fentonova oxidace; degradace; hydrodehalogenace; hydrodechlorace; NaBH4; Na2S2O5; Raneyova slitina Al-Ni